2021
DOI: 10.3389/fcimb.2021.765842
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Oxidation Is Required for Inhibition of Helicobacter pylori Growth, Translocation and Phosphorylation of Cag A

Abstract: Curcumin is a potential natural remedy for preventing Helicobacter pylori-associated gastric inflammation and cancer. Here, we analyzed the effect of a phospholipid formulation of curcumin on H. pylori growth, translocation and phosphorylation of the virulence factor CagA and host protein kinase Src in vitro and in an in vivo mouse model of H. pylori infection. Growth of H. pylori was inhibited dose-dependently by curcumin in vitro. H. pylori was unable to metabolically reduce curcumin, whereas two enterobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Curcumin, a natural polyphenolic compound, has an inhibitory effect on H. pylori growth. H. pylori , unlike other bacteria such as E. coli , fails to evade the inhibitory effects of curcumin due to its inability to reduce this compound [ 5 ]. This is attributed to the absence of the reductase enzyme CurA, suggesting that curcumin reduction may contribute to its inactivity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Curcumin, a natural polyphenolic compound, has an inhibitory effect on H. pylori growth. H. pylori , unlike other bacteria such as E. coli , fails to evade the inhibitory effects of curcumin due to its inability to reduce this compound [ 5 ]. This is attributed to the absence of the reductase enzyme CurA, suggesting that curcumin reduction may contribute to its inactivity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While reduction of curcumin is associated with its reduced activity, oxidation of curcumin has been implicated in its enhanced biological activity. Recently we have shown that curcumin oxidation is essential for inhibiting H. pylori growth, phosphorylation, and translocation of one of its major virulence factors, CagA [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Several studies indicate that these polyphenol compounds positively affect H. pylori eradication. [14][15][16][17][18][19][20][21] However, several experimental and clinical studies have shown different results. 22 23 There are no known meta-analyses concerning the effects of polyphenol compounds on H.pylori infection.…”
Section: Open Accessmentioning
confidence: 99%